MILITARY COMPETITION BETWEEN FRIENDS? HEGEMONIC DEVELOPMENT AND MILITARY SPENDING AMONG EIGHT WESTERN DEMOCRACIES, 1920-1938 - Jari Eloranta (Essays in Economic and Business History, 2001)
This article explores the complicated phenomenon of military spending among a sample of eight Western democracies in the interwar period by analyzing especially the possibility of economic and/or military competition between the Western Great Powers and the ensuing impacts on the smaller states included here. The hegemonic paradigm suggested by e.g. Paul Kennedy predicts that the economic leader in a system will increasingly invest on maintaining security; thus eventually bringing economic growth to a halt. The military spending patterns respective of economic growth at first seem to suggest that not only the totalitarian states, as is the traditional view, but also the UK and France stepped in to fill the void created by the lack of American leadership. However, the military expenditures of these nations were too low to warrant the conclusion that they had any impact on their respective economic performance. This result is also verified here by employing Granger non-causality tests between the military spending and economic growth variables. Moreover, regression analysis on the military spending variables for the UK and France points towards competition on the level. The smaller states, respectively, seemed to follow the UK and France fairly closely in their military spending decisions.